Effects of infusing nitric oxide donors and inhibitors on plasma metabolites, muscle lactate production and meat quality in lambs fed a high quality roughage-based diet. (July 2015) - Cottrell, J.J.; Ponnampalam, E.N.; Dunshea, F.R.; Warner, R.D.
Abstract: As nitric oxide (NO) is postulated to be a mediator of the effects of pre-slaughter stress on meat quality the aims of this experiment were to investigate the effects of modulating NO pharmacologically on meat quality of sedentary lambs. As pharmacological NO donors are prohibitively expensive to use in the lamb modell -Arginine, the substrate for NO synthase (NOS) was infused into lambs and increased NO production by ~ 30%. In a 2 × 2 factorial design we infused eitherl -Arginine (500 mg/kg) or the NOS inhibitor L-N G nitroarginine methyl ester hydrochloride (L-NAME, 30 mg/kg) 190 min pre-slaughter and investigated meat quality in the Longissimus thoracis lumborum (LTL) or Semimembranosus (SM). The principal outcome of the experiment was that L-NAME inhibited proteolysis and reduced tenderness in the SM. These data indicate that events pre-slaughter that affect NO synthesis can influence meat tenderness, potentially via altered muscle metabolism or modulation of proteolytic enzymes. Highlights: Nitric oxide (NO) synthase inhibition increased SM toughness and reduced proteolysis. Infusion of 500 mg/kgl -Arginine increased NO synthesis. Increasing NO synthesis withl -Arginine increased glycogen content.